Invited review: A Review on Field Emission Microscopy, Principles, Theory, and Applications. - Hashim, Khalil I.; Mansouri, Rasha A. (Libyan Journal of Science &Technology, 2025)
The purpose of this paper is to shed light on a very important field of electronic physics which should be known to those who are interested in physics and in electronic physics. The study describes a simple field emission microscope which was designed to permit measurement of electron emission from the whole area of the emitter's surface and a probe hole field emission microscope which was designed to permit measurement of electron emission from individual planes of the emitter's surface. Selection of the planes can be achieved by mechanical, magnetic, or electrostatic deflection of the image onto the probe-hole, which is located in the centre of the screen, and the transmitted current is collected by an electrode sited behind a hole in the centre of the screen. Changes in work function which result from the adsorption of metal atoms on the whole tip and individual planes of the emitter surfaces have been measured by many authors by noting the changes in the slope of Fowler-Nordheim plots. In addition, surface diffusion and desorption of metal atoms from the emitter surface have been investigated and the activation energies for these processes evaluated.